The influence of training and detraining periods on free hormones, body dimensions and explosive power in young soccer players - Moreira, A.; Mortatti, A.; Arruda, A. F. S.; Freitas, C. G.; Aoki, M. S.; Crewther, B. T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Some authors have proposed that testosterone (T) helps to signal acute and chronic changes in neuromuscular capacity for explosive performance (Crewther et al. 2011). During puberty, T increases markedly in boys such that both physical development and performance could be associated with changes in endocrine status (Naughton et al., 2000). However, training factors add to the complexity of understanding the development of young male athletes. Therefore, the study aim was to assess the effect of training and detraining on free hormones, body dimensions and explosive power in elite young soccer players. Methods: 26 elite young (12.7 ± 0.2 yr) soccer players were monitored across a 12-week preparatory training phase, a 7-week competitive and a 2-week detraining phase. Salivary free T and cortisol (C) concentrations, body dimensions and countermovement jump height (CMJ) were assessed before (T1) and after (T2) the pre-season phase, and after the competitive (T3) and detraining phases (T4). As a marker of maturity status, years from peak height velocity (YPHV) was verified. None of the players reached PHV during the study period. Results: Salivary T was higher at T4 compared with T2 and T3 (p < 0.05), but no significant changes in salivary C were noted. Increments in height and body mass were verified throughout the investigation. We also verified significant increments in CMJ height from T2 to T3, but performance declined after the detraining period (to T1 values). Estimated YPHV changes (nearer from estimated PHV) revealed expected maturational development. Discussion: Increases in free T concentrations mirrored expected age-related changes in physical development. The increases in CMJ height and change in years from PHV also coincided with body mass alterations. The detraining phase did not affect morphological and hormonal development, but did influence CMJ performance. Thus, age-related changes in endocrine function and training factors need to be considered in tandem when monitoring youth athletes.